Validated Stability-indicating HPTLC Determination of Baclofen in Bulk Drug, Pharmaceutical Formulations and Real Human Urine and Plasma. - Saleh, Safaa F.; Omar, Mahmoud A.; Derayea, Sayed M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A simple, highly selective and stability-indicating high-performance thin-layer chromatographic method was developed and validated for the analysis of baclofen in bulk powder, pharmaceutical formulations and human urine and in and real human plasma. The method employed TLC aluminum plates precoated with silica gel 60 F254 as the stationary phase. The solvent system consisted of butanol–acetic acid–water (3.0: 0.5: 0.5, v/v/v). This system was found to give compact spots for baclofen (Rf value of 0.54). Densitometric analysis was carried out in the absorbance mode at 238 nm. The linear regression analysis data for the calibration plot showed good linear relationship (r2 = 0.9983) in the concentration range 1.5-7.5 µg per spot. The analytical performance of the method was fully validated, and the results were satisfactory. The limits of detection and quantitation were 0.31 and 1.03 µg per spot, respectively. Baclofen was subjected to acid and alkali hydrolysis, oxidation and photodegradation. The degraded product was well separated from the pure drug. Results indicate that the drug is stable against light and basic conditions. However, additional peaks were observed at Rf value of 0.65 and at Rf value of 0.14 with hydrogen peroxide and hydrochloric acid respectively, indicating that the drug is susceptible to oxidation and acid degradation. The method was applied for the analysis of baclofen in commercial tablets and the results were similar to those obtained using the reference method. As the method could effectively separate the drug from its degradation product, it can be employed as a stability-indicating one. The high sensitivity of the proposed method allowed determination of baclofen in real human urine and plasma.